2017
DOI: 10.1177/2382120517725506
|View full text |Cite
|
Sign up to set email alerts
|

Journeying to the White Coat Ceremony: A description of the people, situations and experiences that inform student visions of the physician they hope to become

Abstract: Little is known about the experiences that influence entering medical students’ internal concepts of themselves as future physicians. During orientation to medical school, students were asked to write stories in response to the cue, “Tell a story about a person or experience that inspired you to consider a career of service in medicine.” Qualitative methodology was employed to analyze 190 student stories. Thematic analysis identified descriptive details about content and allowed comparison between the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…That study revealed that the dental students appreciated the inherent symbolism in the ceremony and found it to be worthwhile. 11 In a study of medical students, Brown et al 15 found that a WCC, held during the students' first week in the course, provided an opportunity to create a culture where professionalism is valued and encourages students to reflect upon the health professional they will become.…”
Section: Meaning Of the Wccmentioning
confidence: 99%
“…That study revealed that the dental students appreciated the inherent symbolism in the ceremony and found it to be worthwhile. 11 In a study of medical students, Brown et al 15 found that a WCC, held during the students' first week in the course, provided an opportunity to create a culture where professionalism is valued and encourages students to reflect upon the health professional they will become.…”
Section: Meaning Of the Wccmentioning
confidence: 99%